2014
DOI: 10.1063/1.4900610
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-vacancy-related relaxation and conduction behavior in (Pb1-xBax)(Zr0.95Ti0.05)O3 ceramics

Abstract: Failure behavior of Pb(Zr0.95Ti0.05)O3 ferroelectric ceramics under shock compression J. Appl. Phys. 113, 183501 (2013); 10.1063/1.4803052 Room-temperature magnetoelectric properties of Fe doped BaZr0.05Ti0.95O3 J. Appl. Phys. 113, 17D918 (2013); 10.1063/1.4795425Thermal stability of piezoelectric coefficients in (Ba1−xCax)(Zr0.05Ti0.95)O3: A lead-free piezoelectric ceramic Appl.(Pb 1-x Ba x )(Zr 0.95 Ti 0.05 )O 3 (x=0, 0.025, 0.05, 0.075 and 0.1) ceramics were prepared via a solid-state reaction route. Low-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(15 citation statements)
references
References 49 publications
(59 reference statements)
0
15
0
Order By: Relevance
“…Variation of the dielectric permittivity as a function of temperature and frequency: c real part and d imaginary part of the dielectric permittivity of a dielectric relaxation at reduced temperature [40,41]. Finally, the imaginary part of the permittivity increases drastically at high temperatures (T > 432 K), which reflects the presence of extrinsic contributions related to the establishment of a significant electrical conductivity [42]. This dielectric investigation, however, confirms that the studied ceramics are ferroelectric at room temperature.…”
Section: Resultsmentioning
confidence: 70%
“…Variation of the dielectric permittivity as a function of temperature and frequency: c real part and d imaginary part of the dielectric permittivity of a dielectric relaxation at reduced temperature [40,41]. Finally, the imaginary part of the permittivity increases drastically at high temperatures (T > 432 K), which reflects the presence of extrinsic contributions related to the establishment of a significant electrical conductivity [42]. This dielectric investigation, however, confirms that the studied ceramics are ferroelectric at room temperature.…”
Section: Resultsmentioning
confidence: 70%
“…Two independent activation energies are obtain for PLT24 and PLT28 ceramics, grains (high frequency) and grain boundaries (low frequency) related activation energies are 1.60 eV and 1.82 eV, 1.15 eV and 1.66 eV respectively. Values of grain boundaries related activation energy are higher than those of grains, this indicate that grain boundaries exhibit higher resistance than grains 43 . For PLT20 and PLT32 ceramic, activation energies are about 1.73 and 1.75 eV respectively.…”
Section: Resultsmentioning
confidence: 87%
“…It is reported that the ionization of oxygen vacancies either singly or doubly ionized create weakly bonded electrons which take part in conduction at relatively higher temperature than room temperature 31 . Singly ionized oxygen vacancies have activation energy in the range of 0.3-0.7 eV while doubly ionized oxygen vacancies need activation energy of 0.7-1.2 eV 32 .…”
Section: Resultsmentioning
confidence: 99%
“…The correlation coefficient value is very close to unity stating the goodness of fitting. 32 . Furthermore, the E a values estimated from conductivity are very close, which recommends that the electrical conductivity and the relaxation process may be endorsed by sort of similar charge carriers 18 .…”
Section: Resultsmentioning
confidence: 99%